2019
DOI: 10.1186/s13756-019-0464-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an antimicrobial stewardship intervention on perioperative antibiotic prophylaxis in pediatrics

Abstract: PurposeThis study aims to determine the effectiveness of an Antimicrobial Stewardship Program based on a Clinical Pathway (CP) to improve appropriateness in perioperative antibiotic prophylaxis (PAP).Materials and methodsThis pre-post quasi-experimental study was conducted in a 12 month period (six months before and six months after CP implementation), in a tertiary Pediatric Surgical Centre. All patients from 1 month to 15 years of age receiving one or more surgical procedures were eligible for inclusion. PAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 18 publications
4
21
2
Order By: Relevance
“…Our previously published article on CP's impact on PAP guideline adherence confirmed other research findings with a significantly increased rate in narrow-spectrum antibiotic usage [8].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our previously published article on CP's impact on PAP guideline adherence confirmed other research findings with a significantly increased rate in narrow-spectrum antibiotic usage [8].…”
Section: Discussionsupporting
confidence: 87%
“…For a detailed description of the CPs, complete with pocket card images, see the previous study [8].…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donà et al noted variability in antibiotic prescribing for AP in their single-center study that evaluated the use of AP in children undergoing surgical procedures. The authors found that in the pre-intervention group, antibiotic selection was inappropriate in 51% of cases, and antibiotics were continued for a prolonged duration in 54.9% of cases [23]. Implementation of a clinical pathway proved to be a useful tool and led to a statistically significant improvement in the selection and duration of AP in pediatric patients; however, there still remained room for improvement of AP compliance in the post-intervention group [23].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that in the pre-intervention group, antibiotic selection was inappropriate in 51% of cases, and antibiotics were continued for a prolonged duration in 54.9% of cases [23]. Implementation of a clinical pathway proved to be a useful tool and led to a statistically significant improvement in the selection and duration of AP in pediatric patients; however, there still remained room for improvement of AP compliance in the post-intervention group [23]. Sandora et al evaluated the national appropriateness of AP in children undergoing common surgical procedures using the Pediatric Health Information System database, and they noted significant variation in the use of AP across the 31 institutions submitting data [24].…”
Section: Discussionmentioning
confidence: 99%